Rancang Bangun Pengisian Air Dengan Dua Ukuran Kemasan Menggunakan Conveyor - Abdurraffi Rivaldi; Ummul Khair; Imran Lubis (Universitas Harapan Medan, 2021)
As the development of technology many tools that use the system control and the microcontroller automatically. One of them is technology that can do charging water automatically. The process of charging the water for this much done in a manual way is still not effective if the user should need time to wait in the charging time of the water is then required an automated tool that is useful to turn off and turn on the pump. In this study be made to the Design of charging the water with two packing size using the conveyor. Conveyor serves as a line drive packaging towards charging with the help of dc motor. This system uses a proximity sensor to detect the presence and height of the packing size. Before the system can run the process, there are ultrasonic sensors that detect the presence of packaging on the conveyor line. This tool also uses a relay to control the conveyor of life and death automatically. Information and conditions contained in the passage of the charging device is displayed by the lcd display i2c